Modeling an Eddy-Current Probe for Damage Detection of Surface Cracks in Metallic Parts. (2016) - Aoukili, Abdeslam; Khamlichi, Abdellatif
Abstract: Surface crack detection in metallic parts was considered through modeling the eddy-current pattern induced by a variable magnetic field. This was undertaken by means of the finite element method under harmonic inductive excitation and stationary conditions. The proposed model included the array excitation coils, the array sensing coils, the tested defected plate and the ambient air. A parametric study was conducted then in order to determine the influence of the work frequency and the position of the receiver coil on voltage variation at its bottom edge. The obtained results have shown that the work frequency has little influence on the results in the investigated range of frequencies. On the opposite the position of the receiver coil was found to have a drastic effect on the voltage variations during scanning. It is then possible to optimize the positions of the receiver coils to provide best sensing in terms of voltage variations when the probe passes over the flaw.